Hubungan Kebiasaan Merokok di dalam Rumah dengan Kejadian Pneumonia pada Balita: Literatur Review - Zhabillah, Shifa; Nurhayati, Siti (Neolectura, 2025)
Pneumonia is an acute respiratory tract infection that affects the lungs and remains one of the leading causes of death among children. It accounts for approximately 14% of all deaths in children under five years of age, with an estimated 740,180 deaths, and about 22% of all deaths among children aged one to five years. The risk factors for pneumonia consist of intrinsic and extrinsic factors. Cigarette smoke is considered an intrinsic risk factor for pneumonia, although it is not a direct cause, as exposure to cigarette smoke can irritate the respiratory tract in susceptible children and increase the risk of pneumonia by up to twofold. This study aims to determine the relationship between smoking habits inside the home and the incidence of pneumonia in toddlers. The method used was a literature review conducted through Google Scholar, including published journals from 2020 to 2025. The results of the literature review indicate a significant relationship between smoking habits inside the home and the incidence of pneumonia in toddlers. Therefore, it can be concluded that exposure to cigarette smoke, both directly and indirectly within the home environment, increases the risk of toddlers developing lower respiratory tract infections such as pneumonia and bronchopneumonia.